Pengaruh Baby Massage Dengan Fennel Oil Terhadap Kualitas Tidur Pada Bayi Usia 3-12 Bulan - Lucia Kenya; Nella Vallen IP; Resa Nirmala Jona (NAJ Nursing Applied Journal, 2024)
Babies need adequate quality sleep because sleep is important for babies to mature their brains. The baby's body will produce growth hormone when sleeping, so the baby needs enough sleep for optimal development. One factor that influences infant development is rest or the length of sleep. To determine the effect of baby massage with fennel oil on the sleep quality of infants aged 3–12 months. Method one group pretest-post-test design. This study consisted of babies who visited intending to do baby massage at the Ananda Ambarawa Baby Spa Clinic in the January-February 2023 period. There were as many as 70 babies, so in a month, there were an average of 35 babies. The sampling technique in this study was purposive sampling, with a population of 35 infants and 32 infants as respondents. The PSQI questionnaire (Pittsburgh Sleep Quality Index) was the research instrument used. Data analysis used the Wilcoxon statistical test. The Wilcoxon statistical test showed that the ρ value was <0.001 <α (0.05). The results of this study indicate that every 1-time baby massage intervention with fennel oil can potentially improve the quality of sleep for babies at 3–12 months of age 4,460 times. This result showed that Ha is accepted. In conclusion, baby massage with fennel oil affects sleep quality in infants aged 3–12 months. It is hoped that midwives can continue to motivate mothers and parents to perform infant massage and can be an additional reference for increasing the knowledge and insights of midwifery students, who are expected to become one of the most effective midwifery interventions to improve infant sleep quality.